Forest Genetics - Research and Application in India forestry - I (Part-I) - Dogra, P. D. (Indian Forester, 1981)
Forest genetic can be highly profitable if used on a wide scale in Indian Forestry. Sufficient genetic diversity exists in Indian tree-species to give us large genetic gains. Improvement potential, using wild gene resources for selection and breeding is vast as there are over 244 genera and 400 forest tree species in India. Of these over 30 species and 22 genera are of outstanding forestry value (Troup, 1921). Selective genetic-variation can be lifted from wild populations, multiplied vegetatively or by seed, and planted with controlled germplasm sources. Among the Indian species no less than 74 reproduce by cutting, 11 by layers, 9 by grafting and buding and 104 by root suckers. More than 161 species coppice vigorously (Rao,1956). Afforestation techniques of over 170 species have been worked out (Ghosh, 1977). Tree genetic approach of survey of natural variability, quick evaluation, selection, conservation, multiplication and planting superior variability, directly in the field can give immediate genetic gains. Short range tree improvement programmes can generate results for incorporation in forestry operations. Intra- and interspecific hybridization experiments can be taken up for future use. This article discusses genetic information on indigenous species for use of Indian Foresters engaged in raising nursery stocks and in tree plantation work. The account is presented in two parts. The first part deals with genetic potential of indigenous species, approach to tree improvement work, natural variation identification selection and conservation of geographic races and trees, cytological and chemical variation and reproductive biology. The second part deals with, genetiC control, through seed, seed orchards vegetative propagation, haploidy and agronospermy. Inra-and interspecific hybridization-potential of indigenous species is also discussed and suggestions on application of forest genetics in Indian Forestry are given in the end.